Introducing urine‑enriched biochar‑based fertilizer for vegetable production: Acceptability and results from rural Bangladesh - Sutradhar, Ipsita; deGrafenried, Meredith Jackson; Akter, Sayema; McMahon, Shannon A.; Waid, Jillian L.; Schmidt, Hans‑Peter; Wendt, Amanda S.; Gabrysch, Sabine (Springer Link, 2022)
This article was published in the Environment, Development, and Sustainability by Springer Link [Copyright © 2021, The Author(s)] and the definite version is available at: https://doi.org/10.1007/s10668-020-01194-y The Journal's website is at: https://link.springer.com/article/10.1007/s10668-020-01194-y